Prioritizing Islamic Financial Literacy for MSMEs in Indonesia - Tubastuvi, Naelati; Rusydiana, Aam Slamet (SMART Insight, 2024)
Islamic financial literacy in Indonesia is still quite low, when compared to financial literacy in general. This study aims to determine the priority of Islamic financial literacy in MSMEs in Indonesia. The method used in this research is Delphi, with research data coming from interviews with academics, practitioners and regulators of finance and Islamic economics in general, totaling 11 respondents. The results of the analysis found that there are 14 variables of Islamic financial literacy problems of MSMEs in Indonesia, and all variables have been agreed upon by economic experts. From the results of the calculation using the Delphi method, there are 3 main priorities for Islamic financial literacy of MSMEs in Indonesia, namely increasing the involvement of MSMEs as agents of Shariah financial literacy, expanding MSME access to the Islamic Financial Institutions (IFIs) sector, and encouraging IFI to develop simple and affordable products.